1991
DOI: 10.1183/09031936.93.04060694
|View full text |Cite
|
Sign up to set email alerts
|

Particle deposition and resistance in the noses of adults and children

Abstract: Nasal filter efficiency for particles has been described by several authors as showing large individual variations, probably somehow related to airflow resistance. Twelve children, aged 5.5-11.5 yrs and 8 aged 12-15 yrs were compared to a group of ten adults. Deposition of polystyrene beads (1, 2.05, 2.8 microns mass median aerodynamic diameter (MMAD] was measured by comparing inhaled aerosols and exhaled air concentrations, for both nose and mouth breathing. Ventilation was controlled to scale breathing patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…However, the feasibility of nasal breathing during exercise should first be considered. Healthy adults spontaneously switch from nasal to oronasal breathing at minute ventilations of 35-45 L‧min −1 (Niinimaa et al 1980;Becquemin et al 1991;Bennett et al 2003). Moreover, without prior habituation, healthy adults can only maintain nasal breathing up to ~ 80% VO 2 max (LaComb et al 2017).…”
Section: Literaturementioning
confidence: 99%
“…However, the feasibility of nasal breathing during exercise should first be considered. Healthy adults spontaneously switch from nasal to oronasal breathing at minute ventilations of 35-45 L‧min −1 (Niinimaa et al 1980;Becquemin et al 1991;Bennett et al 2003). Moreover, without prior habituation, healthy adults can only maintain nasal breathing up to ~ 80% VO 2 max (LaComb et al 2017).…”
Section: Literaturementioning
confidence: 99%
“…This difference can be attributed to the lower deposition in the head for children shown in Supporting Information, Figure S5, allowing more coarse PM to flow into the TB and P regions. Becquemin et al (1991) studied the deposition fractions of size‐segregated PM in the heads of people of different ages using simulation experiments. The results showed that smaller nasal morphology in children did not lead to a greater extrathoracic deposition efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…For application in pediatrics, one needs to consider several developmental factors affecting heat exchange. As the nose enlarges during development, nasal turbinate surface area increases and nasal airway resistance decreases 29 to match the age-dependent increase in basal minute ventilation and the dynamic range required for high levels of exercise as children gain increased mobility. However, neonates and infants do not require such a large dynamic range of humidification capacity.…”
Section: Introductionmentioning
confidence: 99%